Isolation of Flavonoid Compounds from Guava Plant Leaves (Syzygium malaccense (L.) Merr. & Perry) - Lenny, Sovia (Talenta Publisher, 2020)
Isolation of flavonoid compound from the leaves of guava (Syzygium malaccense (L.) Merr. & Perry) has been done using the extraction method. Extract guava leaves separated by using the Column Chromatography method with silica gel as the stationary phase and n-hexane: ethyl acetate (60:40) v/v as the mobile phase. The result of the isolation compound was a yellow crystal with a mass of 39 mg from fractions 325-435, a melting point of 157-159oC, and an Rf of 0.35. The compound was further identified analysis by spectroscopy analysis using Ultraviolet-Visible (UV-Vis), Fourier Transform Infra-Red Spectroscopy (FT-IR), and Proton Nuclear Magnetic Resonance Spectroscopy (1H-NMR). The spectroscopy data of the isolated compound indicated that the compound is a flavonoid named flavonol.